2019
DOI: 10.21608/zumj.2019.16241.1465
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Oesophageal Varices in Cirrhotic Patients by Serum- Ascites Albumin Gradient

Abstract: Background and aim of the work: Portal hypertension (PHT) and the eventual Oesophageal varices is one of the awful complications of liver cirrhosis. Bleeding from OV is a real leading cause of death. This study aims at evaluating serum ascites albumin gradient (SAAG) as a predictor of OV. Patients and methods: A descriptive cross-sectional study was conducted on 105 males and 26 females where they were divided into two main groups and sub groups according to the presence and size of OV. All participants were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
1
0
0
Order By: Relevance
“…Our results are near to the results obtained by Marakbi et al [28] they found that at cut-off value of ≥1.3 gm/dl SAAG could predict the presence of esophageal varices in cirrhotic patients, with specificity (100%), sensitivity (90.09 %), positive predictive value (PPV) was 100% and negative predictive value (NPV) was 64.5%.…”
Section: Resultssupporting
confidence: 79%
“…Our results are near to the results obtained by Marakbi et al [28] they found that at cut-off value of ≥1.3 gm/dl SAAG could predict the presence of esophageal varices in cirrhotic patients, with specificity (100%), sensitivity (90.09 %), positive predictive value (PPV) was 100% and negative predictive value (NPV) was 64.5%.…”
Section: Resultssupporting
confidence: 79%